Ace-1 Target Site Status and Metabolic Detoxification Associated with Bendiocarb Resistance in the Field Populations of Main Malaria Vector, Anopheles stephensi in Iran - Abdollah Badzohre; Mohammad Ali Oshaghi; Ahmad Ali Enayati; Seyed Hassan Moosa- Kazemi; Seyed Hassan Nikookar; Fahimeh Talebzadeh; Nazanin Naseri-Karimi; Ahmad Ali Hanafi-Bojd; Hassan Vatandoost (Tehran University of Medical Sciences, 2024)
Background: Anopheles stephensi is the main vector of malaria in Iran. This study aimed to determine the susceptibility of An. stephensi from the south of Iran to bendiocarb and to investigate biochemical and molecular resistance mechanisms in this species. Methods: Wild An. stephensi were collected from Hormozgan Province and reared to the adult stage. The susceptibility test was conducted according to the WHO protocols using bendiocarb impregnated papers supplied by WHO. Also, field An. Stephensi specimens were collected from south of Kerman and Sistan and Baluchistan Provinces. To determine the G119S mutation in the acetylcholinesterase (Ace1) gene, PCR-RFLP using AluI restriction enzyme and PCR direct-sequencing were performed for the three field populations and compared with the available GenBank data. Also, biochemical assays were performed to measure alpha and beta esterases, insensitive acetylcholinesterase, and oxidases in the strains. Results: The bioassay tests showed that the An. stephensi field strain was resistant to bendiocarb (mortality rate 89%). Ace1 gene analysis revealed no G119S in the three field populations. Blast search of sequences revealed 98-99% identity with the Ace1 gene from Pakistan and India respectively. Also, the results of biochemical tests revealed the high activity of non-sensitive acetylcholinesterase, alpha and beta-esterase in the resistant strain compared to the susceptible strain. No G119S was detected in this study additionally the enhanced enzyme activity of esterases and acetylcholinesterase suggesting that resistance was metabolic. Conclusion: The use of alternative malaria control methods and the implementation of resistance management strategies are suggested in the study area.